DIFFERENCES IN THE RURAL STRUCTURE OF SLOVAKIA IN THE CONTEXT OF SOCIO-SPATIAL POLARISATION - Máliková, Lucia; Klobučník, Michal (Quaestiones Geographicae, 2017)
This study is devoted to socio-spatial polarisation with regard to the rural environment in Slovakia. In fact, ongoing polarisation processes do not take place only in the rural-urban continuum, but within every single category as well. This is evident especially in the rural environment, which has begun to change significantly in terms of its structure and to diversify to a greater extent. As a result, some parts of the countryside began to stagnate and decline gradually. These parts of the rural environment can thus be referred to as marginal, peripheral. With respect to the proclaimed diversity of the rural environment, this study focuses on selected rural structures, namely mountain areas, the borderland, and the area at the intersection of those two structures. Generally, these parts of the rural environment are often confronted with the phenomenon of marginality and peripherality, and because of the given local predisposition are even more vulnerable to its manifestations. Taking into account the dynamism and multidimensional character of this phenomenon, we can further assume that its manifestation changes in time and space. With the use of ANOVA, we examine a set of selected indicators of socio-spatial polarisation and verify whether and to what extent this dynamism depends on the character of diversified rural structures.